Health-care resource use and costs associated with inflammatory bowel disease in northwest London: a retrospective linked database study - Zia UI-Haq; Luiz Causin; Tahereh Kamalati; Durgesh Kahol; Trishan Vaikunthanathan; Charlotte Wong; Naila Arebi (BMC Gastroenterology)
Abstract Background With 20–40% of patients who have inflammatory bowel disease (IBD) not responding to therapy, resource use and costs can be high. We performed a descriptive analysis of health-care data for IBD management in the National Health Service to explore potential areas for improvement. Methods In this exploratory study, we analysed real-world data from the Discover dataset for adults with a diagnosis of incident IBD recorded in northwest London, UK, between 31 March, 2016, and 31 March, 2020. We compared mean visit numbers and primary and secondary care costs per patient to examine resource use and costs for active disease versus remission. Results We included 7,733 patients (5,872 with ulcerative colitis [UC], 1,427 with Crohn’s disease [CD], and 434 with codes for both [termed IBD-undefined in this study]). Remission was recorded in 19,218 (82%) of 23,488 observations for UC, 4,686 (82%) of 5,708 for CD, and 1,122 (65%) for IBD-undefined observations. Health-care resource use was significantly higher with active disease in all settings except primary care for UC. Total health-care costs were greater with active disease than remission for all diagnoses (all p < 0.0001). The main driver of costs was inpatient hospital care among those with active disease; elective inpatient costs were high among patients with UC and IBD-undefined in remission. Conclusions Higher health-care resource use and costs were observed with active disease, which underscores the importance of early induction and maintenance of remission in UC and CD. Updated strategies that incorporate treat to target may offer cost benefits by the offsetting of biologic drug costs with a reduction in costly inpatient hospital stays. Trial registration This trial was not registered as it used pseudonymised retrospective data.